Empowering small-scale industries food safety: Designing fuzzy controlled pulse electric field pasteurization - Ika Noer Syamsiana; Mohammad Wildan Fikri Amrullah; Muhammad Akhlis Rizza; Wahyu Aulia Nurwicaksana; Zakiyah Irfin; Ratna Ika Putri; Cahya Rahmad (Food Chemistry Advances)
The food processing is confronted with significant challenges in the maintenance of food safety and quality. This is particularly the case with the use of heat-based preservation methods, which have the potential to reduce the content of essential nutrients. This study focuses on the design and implementation of pulsed electric field (PEF) system for milk sterilization. The objective is to develop a more efficient and economical alternative solution for milk preservation. PEF technology functions by applying a high-voltage pulse generator is developed using a flyback transformer, with duty cycle and frequency settings determined through the application of fuzzy logic control (FLC). The result is developed in this study capable of producing a variable output voltages within the range of 14.5 kV to 21 .6kV. the production cost of the device was only USD 456.00, a significant reduction compared to the USD 1,843.00 typically required for similar high-voltage pulse generators. This cost-effective solution not only ensure compliance with international food safety standards but also enhanges the global competitiveness of SMEs, positioning them to capitalize on emerging market opportunities.